The Debate at the Beginning of the 21st Century on the Peopling of the Americas - Miotti, Laura Lucia (2012)
No se trata de un verdadero artículo sino de la Introducción a un volumen especial de la revista que forma una suerte de libro editado sobre Poblamiento en América del Sur. A meeting on the late-Pleistocene peopling of the Americas held November 2010 at La Plata, Argentina, was the fifth in a series of international symposia on this topic originally organized by Mexican scholars. This book and the bonds established between archaeologists are two main results this event produced. Both of them are crucial to the development of this area of inquiry and in different ways are relevant to filling the gaps in research on the early peopling of South America and the entire continent. Most of the papers in this book focus on southern South America. (At the conference the geographic focus was better balanced, and several papers on topics from Siberia, North America, and even Australia were presented.